Persepsi remaja terhadap shopee pay later di kota makassar - Indrayanti, Indrayanti; Sennahati, Sennahati; Rintoh, Rintoh (Journal of Communication Sciences (JCoS), 2024)
The purpose of this research is to find out how teenagers in Makassar City perceive the Shopee PayLater credit feature offered by the Shopee e-commerce platform. The study emphasizes how teenagers understand and incorporate these characteristics into their daily lives by using a symbolic interaction approach. The research involved 10 teenagers who actively use Shopee PayLater, aged between 17 and 19 years old. Social interactions, cultural norms, and status symbols associated with modern financial technology heavily influence teenagers' perceptions of Shopee PayLater. Most of the people who responded perceived Shopee PayLater as a useful and valuable tool that helped them manage their finances, enhanced their shopping experience, and fulfilled their life needs and could always keep up with the times.